Effects of Intra-Storm Soil Moisture and Runoff Characteristics on Ephemeral Gully Development: Evidence from a No-Till Field Study - Karimov, Vladimir R.; Sheshukov, Aleksey Y. (My University, 2017)
Ephemeral gully erosion, prevalent on agricultural landscapes of the Great Plains, is recognized as a large source of soil loss and a substantial contributor to the sedimentation of small ponds and large reservoirs. Multi-seasonal field studies can provide needed information on ephemeral gully development and its relationship to physical factors associated with field characteristics, rainfall patterns, runoff hydrograph, and management practices. In this study, an ephemeral gully on a no-till cultivated crop field in central Kansas, U.S., was monitored in 2013 and 2014. Data collection included continuous sub-hourly precipitation, soil moisture, soil temperature, and 15 field surveys of cross-sectional profiles in the headcut and channelized parts of the gully. Rainfall excess from a contributing catchment was calculated with the Water Erosion Prediction Project (WEPP) model for all storm events and validated on channel flow measurements. Twelve significant runoff events with hydraulic shear stresses higher than the critical value were identified to potentially cause soil erosion in three out of fourteen survey periods. Analysis of shear stress imposed by peak channel flow on soil surface, antecedent soil moisture condition, and channel shape at individual events provided the basis on which to extend the definition of the critical shear stress function by incorporating the intra-storm changes in soil moisture content. One potential form of this function was suggested and tested with collected data. Similar field studies in other agriculturally-dominated areas and laboratory experiments can develop datasets for a better understanding of the physical mechanisms associated with ephemeral gully progression.
Citation: Karimov, V.R.; Sheshukov, A.Y. Effects of Intra-Storm Soil Moisture and Runoff Characteristics on Ephemeral Gully Development: Evidence from a No-Till Field Study. Water 2017, 9, 742.
Keywords: Ephemeral gully; Erosion; Sediment transport; Soil moisture; Shear stress; WEPP